Determination of Estragole in Pharmaceutical Products, Herbal Teas and Herbal Extracts Using GC-FID - Omnia A. Ismaiel, Essam Abdelghani, Heba Mousa, Samih I.Eldahmy, B. E. Bayoumy (Journal of Applied Pharmaceutical Science, 2016)
Recent concerns about the potential carcinogenicity of estragole necessitate accurate determination of estragole in different products and extracts. GC-MS method has been used for characterization of Fennel extract; Estragole was found to constitute more than 65% of the extract. Accurate and simple method for the determination of estragole in pharmaceutical products, herbal teas and herbal extracts was developed using GC-FID technique and p-anisaldehyde as an internal standard. Target analyte was extracted from different matrices by applying various extraction procedures such as hydro-distillation and ultrasound-assisted extraction. The hydro-distillation technique provided higher amounts of extracted estragole compared to ultrasound-assisted extraction. The calibration curve showed excellent linearity over a concentration range of 0.1–10 mg/ml with a correlation coefficient of 0.9997. Accuracy of back calculated calibration standards were within ±7.3 %. Precision and accuracy of quality control samples were within ± 9.0 %. Estragole levels were accurately measured in Fennel fruits, Chinese and Japanese Star Anise, Sekem® teabags for cough, Baby Calm® teabags, Balsam®, Guava® syrup for cough and Aqua ream® syrup for diarrhea. Accurate concentrations of estragole should replace the non-specific label information found on most of the tested products.
Keywords: Estragole, fennel, star anise, hydro-distillation, teabags and pharmaceutical products.